PENYULUHAN HUKUM TENTANG UPAYA TINDAK PIDANA NARKOTIKA DI DESA SURABAYA UTARA KECAMATAN SAKRA TIMUR KABUPATEN LOMBOK TIMUR - Firzhal Arzhi Jiwantara; Siti Hasanah; Lukman (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This Community Service activity is motivated by the situation and condition of North Surabaya Village, Sakra Timur District, East Lombok Regency as a partner, which is still rampant in cases of drug trafficking among the youth of the area. Therefore, this is a common problem that must be solved, because the researcher's observations of Narcotics Crime Prevention Efforts will certainly provide understanding and knowledge to the community, especially the youth of North Surabaya Village to minimize the rise of Narcotics Crime crimes which are very negative for the next generation of the nation. This is where the role of the North Surabaya Village government is needed to be a protector and can provide positive activities to village youth through its Karang Taruna institution. The purpose of this study is to find out what factors influence the prevalence of narcotics crime. The type of research used in this research is qualitative research. The nature of the research is descriptive-analytic. Sources of data used are primary data sources obtained from interviews with the village government of North Surabaya, secondary data sources obtained from books and other sources related to research and tertiary data sources. And data collection techniques through observation, interviews and documentation. This study found several factors and regulations for land acquisition for the public interest, as well as the role of the North Surabaya Village government in efforts to prevent narcotics crimes